Student-centered Factors on Online Learning: A Systematic Literature Review - Juliantara, I Putu Eka; Santosa, Paulus Insap; Kusumawardani, Sri Suning (2022)
Along with its growth, one of the research areas to perfect online learning is student-centered factors that affect how online learning is going from the student's perspective. However, online learning still faces similar problems from the student perspective even until the COVID-19 pandemic. This fact confirms researchers still need to do more studies, or educators still need to learn more. So, this study aimed to help researchers and educators by providing the latest and relevant student-centered factors. This study reviewed 21 latest and relevant studies to achieve the objective. As a result, 12 types were discovered, with at least three factors in each factor type. Also, the impact of each factor on each other was given. Then, some factors were prioritized to solve the problems mentioned before. It'll be easier to improve the prioritized factors by taking steps back and improving the independent variables first. Hopefully, researchers can see a gap in those factors and start a study to solve it. Also, educators can learn at once and adjust some relevant factors to facilitate online learning as expected, especially during the COVID-19 pandemic. © 2022 IEEE.